Microstructure and optical properties of TiO2- and HA-coated Ti6Al7Nb alloy by sol-gel method - Tosun, Nihat; Kurmi, Saleh Zakar; Tosun, Gul (Indian Acad Sciences, 2020)
In this study, the combination of titanium dioxide (TiO2) and/or hydroxyapatite (HA) coatings on Ti6Al7Nb titanium alloy to be used as an implant was performed in different solution retention times by the sol-gel dip-coating method and the characterization and optical properties of these coatings were investigated. Two different coatings were made on the substrate, the first group of samples was first coated with TiO2 and then with HA, while the second group of samples was coated with TiO2 alone. Before sol-gel coating, the samples were rinsed in distilled water and dried at 200 degrees C for 2 h. The samples were immersed perpendicular to the coating solution. Thin films were obtained at a draw rate of 2 mm s(-1). Microstructure investigations of the prepared coatings were examined under optical and scanning electron microscopes, while solid-state elemental fractions were determined by energy-dispersive X-ray spectroscopy analysis. Fourier-transform infrared spectroscopy analysis was performed to determine the functional groups placed on the surface of the material. The optical properties of the material were determined by UV analysis.
Keywords: Sol-gel; TiO2; HA; Ti6Al7Nb; microstructure; optical properties